Associated factors in young adults with a family history of high blood pressure and diabetes (Research, Society and Development, 2020)
The aim of the study was to analyze the association between knowledge of family history for chronic diseases, more specifically, SAH and DM, and the lifestyle of young schoolchildren. The methodology of this work is an analytical study, of a quantitative nature, carried out with 1073 young adult schoolchildren from Fortaleza-Ceará. The association of categorical variables was analyzed using the non-parametric tests of x2. Odds ratios (OR) were calculated to estimate the strength of the association, with a 95% confidence interval. As a result of confirming the statistical association of knowledge about family history of hypertension with the sex of young schoolchildren (p = 0.007) and smoking (p = 0.041) in relation to knowledge about family history of diabetes, the variables were statistically significant: smoking (p = 0.026), income (0.042) and physical activity (0.045). In conclusion, the study showed that knowledge of the family history of hypertension and diabetes has intervening factors, such as lifestyle and smoking.